Estudo fitoquímico e de toxicidade (aguda e subaguda) de Celtis iguanaea (Jacq.) Sarg. em ratos Wistar - Froeder, Amanda Luana Forbrig (2015)
The Celtis iguanaea species is popularly known as esporão-de-galo and its leaves are used in folk medicine to treat body aches, rheumatism, asthma, colic, indigestion, ulcers, and as a diuretic, and roots for urinary tract infections. This study aimed to contribute to the phytochemical, antioxidant and antimicrobial study from plant roots, as well as investigated the acute and subacute toxicity of the leaves of C. Iguanaea. The leaves and roots of the plant were dried, triturated and macerated with ethanol (70%) for seven days, with renewal of the solvent. The material was filtered and concentrated in a rotary evaporator to obtain the aqueous extract (AE). Part of the AE roots was taken to complete dryness yielding the crude extract (CE) and the remainder was fractionated successively with dichloromethane (DCM), ethyl acetate (EA) and n-buthanol (BU). All EA leaves was taken to dryness to give EB. In the antioxidant and phytochemical analysis of roots, the EA fraction showed the highest amount of polyphenols (221.55 ± 0.28 mg gallic acid equivalents/g), flavonoids (28.80 ± 0.09 mg quercetin equivalents/g) and alkaloids (3.96 ± 0.32 mg/g) and the best antioxidant capacity by DPPH method (IC50 = 27.97 ± 0.35 μg/mL), TBARS (IC50 = 42.03 ± 4.55 μg/mL) and the reduction of power test (EC50 = 0.86 ± 0.13 mg/mL, but no statistical difference compared to other extracts). This fraction was also capable of removing free radicals significantly through testing of DCFH-DA and able to completely reverse the oxidative damage by protein carbonyl assay. As regards the assessment of the toxicity of the leaves, a single dose of 2000 mg/kg of crude extract administered to rats did not cause mortality or morbidity, so, the extract was classified in categoty 5 (LD50 entre 2000-5000 mg/kg) in accordance with OECD 423. The guide subacute experiment, the animals were divided into four groups: control and experimental (doses of 100, 200 and 400 mg/kg) for 28 days. There was in increase in blood sugar of the animals, indicating a possible pancreatic toxicity. Moreover, enzyme levels and histological analysis indicated that the extract does not hepatotoxic effect, even at the highest dose used. The findings contributed to reveal some phytochemicals and antioxidants characteristics of the species and show that C. iguanaea can be considered safe.